Simultaneous sensing of cysteine/homocysteine and glutathione with a fluorescent probe based on a single atom replacement strategy. Issue 11 (26th February 2021) - Yao, Jingfeng; Yin, Guoxing; Yu, Ting; Li, Haitao; Yin, Peng
Abstract : Novel and simple fluorescent probes are utilized for the simultaneous monitor of Cys/Hcy and GSH. Abstract : In recent years, there have been many reports of fluorescent probes for multi-channel detection of Cys, Hcy and GSH. Particularly, reports of fluorescent probes using NBD (7-nitro-1, 2, 3-benzoxadiazole) or SNBD (7-nitro-1, 2, 3-benzothiadiazole) moieties as fluorophores are particularly common. Unfortunately, their 4-sulfhydryl derivatives exhibited negligible fluorescence, which makes them incapable of detecting GSH directly. Herein, by performing single selenium-for-oxygen atom replacement within 4-chloro-substituted NBD (NBD-Cl), we developed a small molecule fluorescent probe based on a single atom replacement strategy, which enables the probe to be used for simultaneously distinguishing Cys/Hcy and GSH, along with fluorescence imaging of Cys/Hcy and GSH in live cells from red and green emission channels, respectively.